Approaches to Information Integration in Structural Health Monitoring Systems for Bridges - Garita, César (2016)
The design and development of systems aimed at gathering, processing, storing and integrating information associated to periodic monitoring of the condition of civil structures such as buildings and bridges, represent a challenge from a computational point of view. In practice, there exist countless tools and components that may need to be integrated in order to support agile strategic decision making regarding structural health conditions. Many of these computational components may already exist or have been developed by different organizations and present a high level of heterogeneity in terms of data models and software configurations. This paper provides a study of information integration approaches in areas related to structural health monitoring with emphasis on bridge structures. The proposed study aims at putting together experiences that may avoid the “reinvention of the wheel” as well as the identification of differentiating aspects which may serve as a base for innovative approaches for information integration in this area. This work has been carried out as part of the e-Bridge 2.0 research project at the Costa Rica Institute of Technology.